Good Corporate Governance sebagai Prediktor Kinerja Keuangan dan Implikasinya pada kebijakan Dividen - Pradnyani, Ni Luh Putu Sri Purnama; Putra Astika, Ida Bagus; Badera, I Dewa Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2013)
Good corporate governance is a system that regulates and controls the company in order to enhance the image and value of the company. Implementation of good corporate governance that will consistently deliver improved financial performance of the company increased its implications on corporate profits. The higher level of profits from the company, then the decision of dividend distribution to shareholders will be higher. This study aims to determine the effect of the relationship empirically good corporate governance in financial performance and its implications on dividend policy. The study population is a company that makes Corporate Governance Perception Index (CGPI) conducted by the Indonesian Institute for Corporate Governance (IICG) in the year 2007-2011. Sampling technique using purposive sampling with a total sample of 48 companies. The data analysis technique used is multiple linear regression. The results showed that good corporate governance has a positive effect on financial performance. Financial performance has a positive effect on dividend policy while Good corporate governance has no effect on dividend policy. Financial performance mediates the effect of corporate governance on dividend policy. Keywords: corporate governance, financial performance and dividend policy